On establishment and validation of a new predictive model for material removal in abrasive flow machining. (March 2019) - Wei, Haibo; Peng, Can; Gao, Hang; Wang, Xuanping; Wang, Xuyue
Abstract: Abrasive flow machining (AFM) is a non-traditional surface finishing method by extruding abrasive media through workpieces' surfaces. It is difficult to implement uniformity and controllability for material removal in AFM, which makes predictions of material removal and its distribution along media flow direction significantly imperative. In this paper, a new predictive model for material removal in AFM is proposed based-on combination of material removal model for single abrasive and statistics model of active abrasives. To validate its applicability, two experiments are conducted to calibrate the material removal model, and another two experiments are carried out to validate the calibrated material removal model. Results show that this model can predict material removal in terms of profile height variation Δ H and variation trend of mass variation Δ M precisely, with predictive error ( δ error ) of 6.4% and 6.9% achieved in the validation experiments. In the case that the workpiece and flow channel are given, the variation of profile height Δ H on the workpiece surface shows consistent distribution trend with the distribution of the pressure and media flow velocity on the workpiece surface. Highlights: A material removal model is proposed to predict distribution of material removal along flow direction in AFM process. A repositioning method is proposed to gauge material removal by measuring profiles before and after AFM process. Predictions of material removal distribution in terms of profile height variation Δ H are justified by validation experiments. Relationship between distribution of material removal and pressure field of abrasive media flow is established.